Tumoral melanosis mimicking residual melanoma in the setting of talimogene laherparepvec treatment. Issue 10 (28th October 2022) - Park, Song Y; Green, Austin R; Hadi, Rouba; Doolittle-Amieva, Coley; Gardner, Jennifer; Moshiri, Ata S
Abstract : Talimogene laherparepvec (T-VEC) has become an increasingly popular treatment option for surgically non-resectable, recurrent melanoma, usually of cutaneous metastases. The complete response (CR) rate has been reported to be 20% with a median of 9 months to achieve it. In real-world practice, decrease of tumor size often occurs rapidly within the first 2–3 months, while improvement of the pigmentation takes several more months. Such clinical observation of lasting pigmentation could be explained by tumorous melanosis—a histopathological term referring to the presence of a melanophage-rich inflammatory infiltrate without remaining viable tumor cells. Herein, we report six patients with metastatic cutaneous melanoma who were treated with T-VEC. Biopsies were performed after observing clinical responses in the injected tumors. Pathological evaluation demonstrated non-viable or absent tumor tissue with tumorous melanosis in all cases. To accurately assess response to therapy and potentially decrease unnecessary additional T-VEC treatments, serial biopsy of 'stable' lesions should be considered to assess the presence or absence of viable tumor.